Multi-modal magnetic resonance imaging quantifies atherosclerosis and vascular dysfunction in patients with type 2 diabetes mellitus. - Lee, J; Shirodaria, C; Jackson, C; Robson, M; Antoniades, C; Francis, J; Wiesmann, F; Channon, K; Neubauer, S; Choudhury, R (2007)
Vascular magnetic resonance imaging (MRI) is emerging as a powerful research tool. We studied 18 patients with type 2 diabetes mellitus and 20 controls (all with coronary artery disease). MRI measured distensibility, pulse wave velocity (PWV) and atherosclerosis in the aorta, and brachial artery flow-mediated dilatation (FMD). Patients with diabetes showed lower aortic distensibility (2.1 x 10(-3) vs . 3.5 x 10(-3) mmHg-1, p<0.01), faster PWV (8.8 vs ., 6.2 m/s, p<0.01) and impaired FMD (8.5% vs . 13.8%, p<0.05). Diabetes was an independent negative predictor of distensibility. Aortic atherosclerosis was similar in the two groups. There was a negative correlation between aortic distensibility and atherosclerosis in control subjects only, suggesting that other factors such as protein cross-linking may explain lower aortic distensibility in diabetes. MRI provides comprehensive vascular phenotyping in patients with type 2 diabetes and is likely to be useful in studies of disease progression and drug therapy.